AUDIT COMMITTEE AND ACCOUNTING INFORMATION VALUE RELEVANCE - krismiaji krismiaji (SUBSTANSI, 2020)
This paper describes the results of empirical research investigated the effect of audit committee characteristics (AC) on the accounting information value relevance (VR) for Indonesian companies in 2014 - 2018. VR is measured using the Ohlson Model, while AC is measured using its members and its independence members. By using data of 590 firm-years, this study found that the size of the committee audit and the AC independence positively affects the value relevance of EPS. Yet, the AC size affects negatively the BVS value relevance whereas the AC independence does not affect BVS value relevance. These results enrich the literature of value relevance, especially in connection to the AC characteristics.